A Blockchain Semantic-based Approach for Secure and Traceable Agri-Food Supply Chain - Annane, Boubakeur; Alti, Adel; Lakehal, Abderrahim (Engineering, Technology & Applied Science Research, 2024)
Ensuring food security is crucial for maintaining food quality and enhancing consumer services by guaranteeing both safety and satisfaction. However, traditional methods to ensure food security are often susceptible to various forms of fraud and require significant processing overhead, making them inefficient for the evolving demands of modern food supply chains. To address these shortcomings, blockchain technology has emerged as a robust and efficient solution to enhance food security. This paper presents a novel lightweight blockchain-based signature mechanism designed for the rapid detection of food fraud. It also includes a domain-specific ontology to serve as a structured knowledge model, allowing systematic analysis and detection of different types of fraud within the food supply chain. This approach uses smart contracts built on lightweight blockchain technology to initiate and manage transactions related to food fraud. Then, semantic rules are applied to detect and identify fraudulent activities. Once fraud is detected, associated transactions are encrypted and tracked, ensuring visibility and traceability among consortium members. Experimental results based on large-scale transaction data demonstrated ~7.5× speed improvement over iterative search algorithms while maintaining high transaction traceability and significantly reducing storage costs.